Exploring the Attitude of Secondary School Principals towards the Teachers’ Code of Ethics Practice in India - Joshi, K. M.; Ahir, Kinjal; Bhatta, Dharma Dev; Priya, Ashutosh; Shah, Sachin (Journal of Durgalaxmi, 2025)
This study examines how secondary school principals in India perceive the implementation of the teachers’ code of ethics, considering variables such as gender, type of school, professional experience, and age. A cross‑sectional questionnaire‑based research design was employed, utilising a five‑point Likert scale to capture attitudes regarding teachers’ ethical practices. Data from 76 principals were analysed using descriptive statistics, independent‑samples t‑tests, and one‑way ANOVA in Jamovi software at a 95 per cent confidence level (p ≤ 0.05). The findings reveal no statistically significant differences in attitude scores across gender, school type, age group, or length of administrative experience. Overall, principals displayed a positive stance towards ethical conduct among teachers. The study contributes to educational ethics literature by contextualising school leaders’ perceptions and suggests professional development measures to reinforce ethical practices within Indian secondary education.